Human Postural Control - Ivanenko, Yury; Gurfinkel, Victor S. (Frontiers in Neuroscience, 2018)
From ancient Greece to nowadays, research on posture control was guided and shaped by many concepts. Equilibrium control is often considered part of postural control. However, two different levels have become increasingly apparent in the postural control system, one level sets a distribution of tonic muscle activity (‘posture’) and the other is assigned to compensate for internal or external perturbations (‘equilibrium’). While the two levels are inherently interrelated, both neurophysiological and functional considerations point towards distinct neuromuscular underpinnings. Disturbances of muscle tone may in turn affect movement performance. The unique structure, specialization and properties of skeletal muscles should also be taken into account for understanding important peripheral contributors to postural regulation. Here, we will consider the neuromechanical basis of habitual posture and various concepts that were rather influential in many experimental studies and mathematical models of human posture control.